Integrated Effect of Water Harvesting and Manuring on Growth and Establishment of Prosopis cineraria (Khejri) in Hot-arid Region of Rajasthan - Gupta, J. P.; Sharma, A. K (Indian Forester, 1998)
Scarcity of water during tree establishment can be overcome by making circular catchment around the tree seedling. Integration of treatments viz. catchment area and farm yard manure was done to test the increase in profile moisture and ultimately increase in survival and growth of Prosopis cineraria , an important multipurpose tree of desert ecosystems. The results of the field experiment showed that after 36 months of planting there was a four fold increase in plant height with catchment area of 12.6 m2 as compared to control. Farm Yard Manure (FYM) was not found effective statistically. Also no interaction effect was observed in the different combination of the levels of both the two factors i.e. catchment size and FYM application.